Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

Select the correct answer.

Which function defines [tex]\((f+g)(x)\)[/tex]?

[tex]\[
\begin{array}{l}
f(x)=\frac{5}{x}+12 \\
g(x)=\sqrt{x-3}+10
\end{array}
\][/tex]

A. [tex]\((f+g)(x)=\frac{5}{x}-\sqrt{x-3}+2\)[/tex]

B. [tex]\((f+g)(x)=\frac{\sqrt{x-3}+5}{x}+22\)[/tex]

C. [tex]\((f+g)(x)=\frac{5}{x}+\sqrt{x}+19\)[/tex]

D. [tex]\((f+g)(x)=\frac{5}{x}+\sqrt{x-3}+22\)[/tex]


Sagot :

To determine which function defines [tex]\((f+g)(x)\)[/tex], we start by understanding the operations of [tex]\(f(x)\)[/tex] and [tex]\(g(x)\)[/tex] individually.

Given:
[tex]\[ f(x) = \frac{5}{x} + 12 \][/tex]
[tex]\[ g(x) = \sqrt{x-3} + 10 \][/tex]

The composition [tex]\((f+g)(x)\)[/tex] is the sum of [tex]\(f(x)\)[/tex] and [tex]\(g(x)\)[/tex]:

[tex]\[ (f+g)(x) = f(x) + g(x) \][/tex]

Step-by-step:

1. Add [tex]\(f(x)\)[/tex] to [tex]\(g(x)\)[/tex]:
[tex]\[ f(x) = \frac{5}{x} + 12 \][/tex]
[tex]\[ g(x) = \sqrt{x-3} + 10 \][/tex]

So,
[tex]\[ (f+g)(x) = \left( \frac{5}{x} + 12 \right) + \left( \sqrt{x-3} + 10 \right) \][/tex]

2. Combine like terms:
[tex]\[ (f+g)(x) = \frac{5}{x} + 12 + \sqrt{x-3} + 10 \][/tex]

Simplify this further:
[tex]\[ (f+g)(x) = \frac{5}{x} + \sqrt{x-3} + 22 \][/tex]

Thus, the correct function that defines [tex]\((f+g)(x)\)[/tex] is:
[tex]\[ D. \left( f+g \right)(x) = \frac{5}{x} + \sqrt{x-3} + 22 \][/tex]